Rock sport climbing : techniques and tricks - Willett, Edward, 1959- (New York : Rosen Pub. Group, 2003)
Describes the basics, techniques, gear, safety aspects, and competitions of rock climbing.
Includes bibliographical references (p. 45-46) and index.
Keywords: Rock climbing -- Juvenile literature; Rock climbing